Transgenerational Sex-dependent Disruption of Dopamine Function Induced by Maternal Immune Activation - Santoni, Michele; Frau, Roberto; Pistis, Marco (Frontiers in Pharmacology, 2022)
Several epidemiological studies suggest an association between maternal infections during pregnancy and the emergence of neurodevelopmental disorders in the offspring, such as autism and schizophrenia. Animal models broadened the knowledge about the pathophysiological mechanisms that develop from prenatal infection to the onset of psychopathological phenotype. Mounting evidence supports the hypothesis that detrimental effects of maternal immune activation might be transmitted across generations. Here, we explored the transgenerational effects on the dopamine system of a maternal immune activation model based on the viral mimetic polyriboinosinic-polyribocytidilic acid. We assessed dopamine neurons activity in the ventral tegmental area by in vivo electrophysiology. Furthermore, we studied two behavioral tests strictly modulated by the mesolimbic dopamine system, i.e., the open field in response to amphetamine and the prepulse inhibition of the startle reflex in response to the D2 agonist apomorphine. Second-generation adult male rats did not display any deficit in sensorimotor gating; however, they displayed an altered activity of ventral tegmental area dopamine neurons, indexed by a reduced spontaneous firing rate and a heightened motor activation in response to amphetamine administration in the open field. On the other hand, second-generation female rats were protected from ancestors' polyriboinosinic-polyribocytidilic acid treatment, as they did not show any alteration in dopamine cell activity or in behavioral tests. These results confirm that maternal immune activation negatively influences, in a sex-dependent manner, neurodevelopmental trajectories of the dopamine system across generations.